Ornithine decarboxylase expression in the small intestine of broilers submitted to feed restriction and glutamine supplementation - Fischer da Silva, AV; Borges, SA; Maiorka, A; Givisiez, PEN [UNESP]; Rocha, C; Macari, Marcos [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2007)
Six hundred and forty one-day-old Cobb male broilers were used to evaluate ornithine decarboxylase (ODC) expression in the mucosa of the small intestine. Birds were submitted to early feed restriction from 7 to 14 days of age. The provided feed was supplemented with glutamine. A completely randomized design with a 2 x 2 factorial arrangement was used (with or without glutamine, with or without feed restriction). Restricted-fed birds were fed at 30% the amount of the ad libitum fed group from 7 to 14 days of age. Glutamine was added at the level of 1% in the diet supplied from 1 to 28 days of age. Protein concentration in the small intestine mucosa was determined, and ODC expression at 7, 14, 21, and 28 days of age was evaluated by dot blotting. ODC was present in the mucosa of broilers, and the presence of glutamine in the diet increased ODC activation. Glutamine prevented mucosa atrophy by stimulating protein synthesis, and was effective against the effects of feed restriction. Dot blotting can be used to quantify ODC expression in the intestinal mucosa of broilers.
Keywords: Feed nutrition; glutamine; intestinal mucosa; mucosa growth; ornitine decarboxylase